The Diversification Benefits of Free Trade in House Value - M.I. Dröes; Harry Garretsen; Walter J.J. Manshanden (Utrecht University, Utrecht School of Economics, Tjalling C. Koopmans Research Institute, 2012)
This paper finds that homeowners could substantially reduce house price risk if they would reinvest their housing wealth in a market portfolio of houses. Free trade in the value of the house among homeowners would allow them to do so. To quantify the diversification benefits of free trade in house value, we estimate simple CAPM and APT models based on a detailed panel dataset of house price changes in the Netherlands. We find that about 92 to 96 percent of house price risk is diversifiable. In most cases, these diversification benefits outweigh the hedging effectiveness of house price futures.
Keywords: 330; house price risk; free trade; financial market; diversification; futures